Correlation between resistance to trastuzumab and miR-141 relative expression in the BT-474 human breast cancer cell line - Zohreh Rezaei; Dor Mohammad Kordi-Tamandani; Ahmadreza Sebzari; Kazem Dastjerdi (مجله دانشگاه علوم پزشکی بیرجند, 2017)
Background and Aim: Resistance to trastuzumab has been a critical barrier to targeted therapy of HER 2-positive (Human Epidermal Growth Factor Receptor 2) breast cancers. MicroRNAs (miRNAs) are known as decisive core regulators of drug resistance that modulate the epithelial-to-mesenchymal transition (EMT) and cancer-related immune responses. The present study aimed at examining the expression of miR-141 in trastuzumab-resistant and trastuzumab-sensitive BT-474 breast cancer cells. Materials and Methods: In this experimental study, trastuzumab-resistant BT-474 cells were generated by continuous in-vitro culture of BT-474 cells in the presence of trastuzumab for six months. The relative expression of miR-141 to U6 RNA was then evaluated in trastuzumab-resistant and trastuzumab-sensitive cells using Relative Real-Time PCR. Mann-Whitney test was used to compare the difference between the two groups. Results: There was a significant difference between the survival rates of resistant BT-474 cells and sensitive cells in the MTT test in the presence of different concentrations of trastuzumab showing that BT-474 breast cancer cells have turned resistant to this drug under long-term culture (P=0.001). Also, the expression of miR-141 in trastuzumab-resistant cells was significantly reduced by four times compared with the BT-474 parent cells (P=0.049). Conclusion:  Down-regulation of miR-141 in trastuzumab-resistant BT-474 cells might be one possible mechanism for resistance against trastuzumab and an indication of the role of this microRNA in controlling the metastasis pathway.